Efektivitas Pelayanan Publik dalam Pembuatan Paspor di Kantor Imigrasi Kelas II Non TPI Blitar - Ardin Sheylla Yolanda; Wydha Mustika Maharani; Hery Basuki (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Immigration Office Class II Non TPI Blitar is an implementation in the field of immigration at the Regional Office of the Ministry of Law and Human Rights of East Java Province which is responsible to the Head of the Regional Office. Passport is a document that contains identity to enter the border of a country. In the implementation of passport making services at the Blitar Class II Non TPI Immigration Office, researchers found obstacles experienced by applicants such as the information provided was not clear, so the applicant had to return to the Blitar Class II Non TPI Immigration Office, because there was no delivery service for applicants who lived outside Blitar, the priority service room was underutilized due to lack of employees. Therefore, effectiveness in the implementation of public services is very necessary, because one of the requirements for implementing a program to improve the quality of public services. This study aims to analyze the making of passports at the Blitar Class II Non TPI Immigration Office. The method used in this research is descriptive qualitative method. Data collection techniques in this study used observation, interviews, and documentation methods. Public services in passport making at the Immigration Office Class II Non TPI Blitar show some positive results. The implementation of this program includes various services such as passport issuance in the office, out-of-office services, as well as special programs such as Sambang Haji and Sambang Sakit Services. However, there are several obstacles such as the lack of employees in the priority service room, unclear information, and instability in the Community Satisfaction Index (IKM).